Influence of cycling frequency and testing volume on the VHCF properties of 18Ni maraging steel. (July 2019) - Fitzka, Michael; Pennings, Bert; Karr, Ulrike; Schönbauer, Bernd; Schuller, Reinhard; Tran, Minh-Duc; Mayer, Herwig
Highlights: Maraging steel fails from aluminate and Zr(N, C) inclusions in the VHCF regime. Fracture mechanics concept explains the influence of inclusions on cyclic strength. Size effect is caused by volume influence on distribution of inclusion sizes. No frequency effect exists between tests at 95 Hz and 20 kHz. Abstract: Fatigue properties of nitrided 18Ni maraging steel sheets under cyclic tension loading were investigated at cycling frequency 95 Hz by using a resonance tester and at 20 kHz using ultrasonic fatigue testing equipment. High and very high cycle fatigue (VHCF) tests have been performed with two specimen shapes with distinctly different stressed volumes. Fatigue cracks started at internal aluminate or Zr(N, C) inclusions. Inclusions are considered as initial cracks, and fatigue lifetimes as the numbers of cycles necessary to propagate the cracks to fracture. Specimen size effect is explained with volume influence on statistical distribution of inclusion sizes. Comparable mean lifetimes for the same specimen shape and similar dependence of lifetimes on stress intensity factor range were found at 95 Hz and 20 kHz, which indicates the absence of frequency effects in maraging steel.